Pengaruh Game Online terhadap Perbendaharaan Kata Siswa di Sekolah Dasar - Sunandari Sunandari; A.Alya Nurhudayah; Dea Ayuni; Nuramelia Baharuddin (Departement of Mathematics Education, 2023)
This study aims to find out how the influence of online games on students' vocabulary in elementary schools. This research method uses a qualitative approach method. The target in this study were three elementary school children who played online games. The data collection technique used in this study was observation (observation) for two days and interviews. Based on the results of interviews and observations that the researchers conducted on three elementary school-age children who used online games, the researchers found positive and negative effects. These positive influences include children who understand technology, children understand how to access and download online games and also understand vocabulary in foreign languages. As for the negative influence of online games on children in elementary schools, the characters who are free and uncontrolled when playing games are carried over to the real world.